SAT0176 Thyroid and bone metabolism. (1st June 2001) - Bernardes, M; Bernardo, A; Vaz, C; Ramires, M; Mariz, E; Brandão, F; Valente, P; Lopes-Vaz, A
Abstract : Background: Hyperthyroidism (HT) is a risk factor for osteoporosis (OP). It is still uncertain if bone mass and bone turnover are completely normalised after treatment of HT. Objectives: The aim of the present cross-sectional study was to investigate whether former hyperthyroid patients have an increased risk for OP due to reduced bone mass and/or persisting high bone remodelling activity after euthyroidism was restored. Methods: We studied 53 formerly hyperthyroid females (age39 ± 13 years;20 premenopausal (premw); 33 postmenopausal (posmw), who had been euthyroid for a mean period 129 ± 78 months. They were treated by combined medical therapy.we evaluated bone mineral density (BMD) with Lunar4500 DEXA and calcaneal quantitative ultrasound (QUS) parameters with Osteometer DTUone. Biochemical markers of bone turnover (serum osteocalcin (OC), beta-crosslaps (BCL) and urinary deoxypiridinoline (U-DPR) and cross-linked N-telopeptides of type I collagen (NTX), thyroid hormones and antithyroid antibodies (atb) were measured. Results: Considering DEXA parameters, in posmw, 18% had vertebral OP and 7%had hip OP. A higher prevalence of OP was detected by QUS evaluation:39%BUA tscore«-2, 5sd and 42%SOStscore«-2, 5sd. There were no cases of OP in premw. Abnormally high levels of U-NTX (35%premw, 61%posmw), U-DPR (26% premw, 15% posmw) and BCL (26% premw, 52% posmw) were found. Significant correlations were detected between U-NTX and TSH (p < 0, 05, r = -0, 45), U-NTX and free T3 in premw (p < 0, 05, r = 0, 47), BCL and antithyroidperoxidase atb (p < 0, 05, r = 0, 56), BCL and antithyroglobulin atb in posmw (p = 0, 001, r = 0, 59), OC and antithyroglobulin atb in posmw (p = 0, 001, r = 0, 60) and OC and antithyroidperoxidase atb in posmw (p < 0, 001, r = 0, 64). There was no correlation between these biomarkers and dose or duration of thyroxin replacement therapy. Conclusion: The prevalence of OP in former hyperthyroid women wasn`t superior to the general population. There was no significant difference of BMD(Zscores«-2, 5 = 0), although these women presented increased bone resorption markers. The discrepancy between DEXA and QUS could reflect differences in "bone quality". Curiously, dispite being euthyroid, the correlation between U-NTX and TSH could signify that TSH levels close to inferior limit of normality are associated with an increased bone turnover. There is also no explanation to the correlation between biomarkers and antithyroid atbs, but we can`t exclude a possible role of this atbs in the production of BCL or OC. References: Langdahl, et al . Bone mass, bone turnover, body composition and calcium homeostasis in former hyperthyroid patients treated by combined medical therapy. Thyroid 1996;6(3):161–8 Grant, et al . Is previous hyperthyroidism still a risk factor for osteoporosis in post-menopausal women? Clin Endocrinol. 1995;43:339–45